2006
DOI: 10.1093/eurheartj/ehl305
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and heart failure

Abstract: Heart failure is associated with increased risk of venous thromboembolism, stroke, and sudden death. Platelet abnormalities have been well described in heart failure but the significance of platelets in contributing to the thromboembolic complications of heart failure remains uncertain. Furthermore, the role of antiplatelet agents in heart failure remains unclear. This review will focus on platelet activation and the role of platelet dysfunction in heart failure, with particular regard to pathophysiology and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
95
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 71 publications
4
95
0
2
Order By: Relevance
“…However, few studies have explored the prognostic value of baseline platelet counts in patients who underwent VRS, especially in the context of RHD. Patients with RHD frequently experience cardiac insufficiency, in which the platelets are overactivated and then aggregate 1, 9. Excessive consumption would cause a decrease in platelet counts.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have explored the prognostic value of baseline platelet counts in patients who underwent VRS, especially in the context of RHD. Patients with RHD frequently experience cardiac insufficiency, in which the platelets are overactivated and then aggregate 1, 9. Excessive consumption would cause a decrease in platelet counts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is evidence that sympathetic activity induces a procoagulant response (6). Hence, the sympathetic hyperactivity could be an important contributor to the prothrombotic state in HF (1,2). This study showed that, compared with metoprolol, carvedilol resulted in lower cardiac sympathetic activity and lower VWF levels.…”
Section: Discussionmentioning
confidence: 64%
“…Hear t failure (HF) is associated with a prothrombotic state, reflected by an increased risk of arterial and venous thromboembolic events (1)(2)(3)(4). The estimated annual incidence of thromboembolic events is 3%-5% (2,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There was no study comparing MPV levels in patients with idiopathic and ischemic CMP. The blood stasis caused by a dilated chamber and poorly contracting ventricle might be a facilitating or triggering factor on platelet behavior, leading to the stimulation of the platelets and finally an increase in MPV (7,(26)(27)(28). The course of CMP, regardless of the etiology, is the result of the dilated chamber and low LV ejection fraction.…”
Section: Ischemic Cmp Controlsmentioning
confidence: 99%